Central European Functional Programming School : 6th Summer School, CEFP 2015, Budapest, Hungary, July 6-10, 2015, Revised selected papers /: 6th Summer School, CEFP 2015, Budapest, Hungary, July 6-10, 2015, Revised selected papers. (2019) - Unknown
No abstract available